Public women in british India : icons and The urban stage - Rimli Bhattacharya (New York : Routledge, 2018)
It looks at the emergence of the stage actress as an artist and an ideological construct at critical phases of performance practice in British India.
Includes bibliography and index.
Keywords: Gender Studies; PERFORMING ARTS - Theater - General